Microtransaction Game Items inMobile Legends:A Fiqh Al-MuamalatPerspective on Digital Commodities and Gambling Elements - Muhammad Muizzuddin Mohd Rizal; Setiyawan Gunardi (azkiyyah Global Enterprise, 2026)
Non-Indexed Publication